Antibiotic-Coated Intramedullary Nailing Managing Long Bone Infected Non-Unions: A Meta-Analysis of Comparative Studies - Amirhossein Ghaseminejad-Raeini; Alireza Azarboo; Kasra Pirahesh; Amirmohammad Sharafi; Amir Human Hoveidaei; Basilia Onyinyechukwu Nwankwo; Abhijith Annasamudram; Janet D. Conway (MDPI AG, 2024)
Long bone infected non-unions are such an orthopedic challenge that antibiotic-coated intramedullary nailing (ACIN) has become a viable therapeutic option for their management. This study aims to provide a comprehensive assessment of the available data about the use of antibiotic-coated nailing in the treatment of long bone infected non-unions. Following the PRISMA guideline in this meta-analysis, a systematic literature search was conducted across major databases for studies evaluating ACIN in long bone infected non-unions. The primary outcome measures included union rates, infection control, complications and functional status. Five eligible studies encompassing 183 patients in total met the inclusion criteria. The meta-analysis revealed no difference in the union rate in the antibiotic-coated intramedullary nailing group compared to that of the control group (OR = 1.73 [0.75-4.02]). Antibiotic-coated intramedullary nailing demonstrated no association with higher infection eradication (OR = 2.10 [0.97-4.54]). Also, functional outcome measure was mostly not significantly different between ACIN and control interventions. According to this meta-analysis, compared to the management of controls, ACIN is neither linked to increased union rates nor decreased infection rates. The paucity of research on this topic emphasizes the continuous need for additional well-designed randomized controlled trials for the application of antibiotics-coated intramedullary nailing in long bone non-unions.